2012
DOI: 10.1056/nejmoa1114635
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal-Cancer Incidence and Mortality with Screening Flexible Sigmoidoscopy

Abstract: Background The benefits of endoscopic testing for colorectal-cancer screening are uncertain. We evaluated the effect of screening with flexible sigmoidoscopy on colorectal-cancer incidence and mortality. Methods From 1993 through 2001, we randomly assigned 154,900 men and women 55 to 74 years of age either to screening with flexible sigmoidoscopy, with a repeat screening at 3 or 5 years, or to usual care. Cases of colorectal cancer and deaths from the disease were ascertained. Results Of the 77,445 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
586
6
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 884 publications
(625 citation statements)
references
References 38 publications
9
586
6
11
Order By: Relevance
“…Early detection through screening has been shown to be cost-effective (Tappenden et al, 2007) and effective in reducing CRC mortality (Hewitson, Glasziou, Irwig, Towler, & Watson, 2007;Schoen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Early detection through screening has been shown to be cost-effective (Tappenden et al, 2007) and effective in reducing CRC mortality (Hewitson, Glasziou, Irwig, Towler, & Watson, 2007;Schoen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Screening for CRC has been shown to decrease CRC mortality for average risk as well as high-risk individuals (Atkin et al 2010;Hardcastle et al 1996;Hewitson et al 2008;Kronborg et al 1996;Mandel et al 1993;Schoen et al 2012). The American College of Physicians (ACP) recommends that clinicians assess risk for CRC in all adults, and that average-risk individuals screen for CRC using fecal occult blood testing (FOBT) annually, flexible sigmoidoscopy every 5 years, or optical colonoscopy every 10 years, beginning at age 50 and continuing until age 75 (Qaseem et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The endoscopic removal of pre-malignant lesions also reduces the incidence of CRC by avoiding the progression to cancer. Randomized trials in people of average risk invited to participate in screening have shown a reduction in CRC incidence [4][5][6][7] and mortality [4,[7][8][9][10].The EU recommends population-based screening for breast, cervical and colorectal cancer using evidence-based methods with quality assurance of the entire screening process [11]. The EU policy takes into account the principles of cancer screening developed by the World Health Organization [12] and the extensive experience in the EU in piloting and implementing population-based cancer screening programmes [13].…”
mentioning
confidence: 99%